Community pharmacy ethical practice in Jordan: assessing attitude, needs and barriers - Al-Qudah RA; Tuza O; Tawfiek H; Chaar B; Basheti IA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Having a local code of ethics, based on moral obligations and virtues, known to all practicing pharmacists is important in order to guide them in relationships with patients, health professionals, and society. Objective: To investigate pharmacists' attitude and barriers towards applying the ethical principles published by the Jordanian Pharmacists Association in the Jordanian code of ethics. Methods: The study objectives were addressed in a cross-sectional study completed by a convenience sample of community pharmacists, in both cities; Amman and Irbid A questionnaire was used to achieve the study objective. The questionnaire was developed and validated, investigating pharmacists' socio-demographic and practice characteristics, perceived attitude toward certain practice scenarios, and perceived barriers towards applying the locally published ethical principles while dealing with their patients. The questionnaire was self-completed by pharmacists between January and August 2017. Collected data was analyzed using SPSS version 21. Descriptive statistics and parametric tests were used with p<0.05 set a priori as significant. Results: Seven hundred and four pharmacists (Amman n=486; Irbid n=218) responded to the questionnaire, providing completely answered questionnaires with a response rates of 69.4% in Amman and 99.6% in Irbid. Pharmacists from both cities revealed that they use the Internet as their main resource to obtain ethical information when they need it, to help them deal with their patients (34.0% from Amman and 31.5% from Irbid). More pharmacists in Amman (57.0%) had access to resources regarding ethical information at their practice sites compared to pharmacists in Irbid (24.0%). Significant differences in attitude was found between pharmacists practicing in both cities, as significantly less pharmacists from Amman (37.8%) declared that they would sell a medication for an unreported indication according to national and international guidelines, if recommended by the consultant, compared to pharmacists from Irbid (77.7%, p<0.001). Conclusions: Despite having ethical guidance from the Jordanian Pharmacists Association, the majority of pharmacists in Jordan do not use this resource; instead, most choose to access ethical guidance on-line. Pharmacists from the capital, Amman, reported to adhere more with the guidelines when selling a medication for an unreported indication compared to pharmacists from the smaller city, Irbid. Results of this study call for more actions from the authorities in the country responsible for setting and enforcing the pharmaceutical Code of Ethics.